Effect of restaurant consumers’ anticipated emotions on perceived value and behavioral intention in the COVID-19 context - Jiang, Yanmei; Lau, Antonio K. W. (Frontiers in Psychology, 2022)
While hospitality scholars have been conducting research on post-pandemic consumption recovery, the impact of the psychological consequences of COVID-19 on consumers’ post-pandemic behavior remains insufficiently addressed. Therefore, the purpose of this study is to explore the relationships among anticipated emotions, perceived value, perceived threat, and dining-out intention in the COVID-19 context. In this study, 621 restaurant consumers in China were surveyed and the data were analyzed with structural equation modeling. The results suggested that positive anticipated emotions affect perceived hedonic, utilitarian, and social values, whereas negative anticipated emotions affect hedonic value. Hedonic and utilitarian values then influence dining-out intention. Perceived threat in terms of perceived severity and susceptibility to COVID-19 was explored to moderate the impacts of hedonic and social values on the intention. This study contributes to the literature by identifying the positive, distinct roles of both anticipated emotions on consumer dining-out intention through perceived values and threats during the early recovery of COVID-19.